Conchal setback without resection in prominent ear deformity - Karacaoğlan, Naci; Keskin, Mustafa; Çığşar, Bülent (Springer, 2013)
Prominent ear deformity is a congenital anomaly characterized by the absence of an adequate antihelical fold, an increased conchal-mastoid angle, and conchal hypertrophy. In order to overcome the conchal hypertrophy and increased conchal-mastoid angle, either conchal cartilage excision or conchal-mastoid suture placement or posterior auricular muscle manipulations are currently used. The authors present an assessment of a combined technique for the correction of prominent ears with conchal hypertrophy. In this technique through a cartilage incision, a setback is obtained by overlapping the cartilage segments, and the antihelix is formed by Mustarde’s sutures. The conchal setback combined with other techniques may be used as a standard procedure in the surgical treatment of prominent ears with predominance of the conchal component.
Keywords: Conchal Setback; Without Resection; Prominent Ear Deformity